1978
DOI: 10.2466/pms.1978.47.3.857
|View full text |Cite
|
Sign up to set email alerts
|

Eyes as the Center of Focus in the Visual Examination of Human Faces

Abstract: An experiment was conducted to determine the degree to which individuals focus upon the eye region of others while visually inspecting their faces. Using an eye-tracking camera, 16 male subjects spent approximately 40% of their looking time focused upon the eye region of facial photographs, with each of the remaining parts of the face being looked at less.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
103
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(128 citation statements)
references
References 6 publications
17
103
1
Order By: Relevance
“…Prior work suggests that typical individuals attend to the eyes when scanning faces (Haith et al 1977) as well as the internal features of the face (Janik et al 1978;Walker-Smith et al 1977). Furthermore, eye movements become more predictable with increased exposure and familiarity (Althoff and Cohen 1999), suggesting that exposure to a face can influence eye movements, or patterns of attention to faces.…”
Section: Eye Tracking and Familiar Facesmentioning
confidence: 99%
“…Prior work suggests that typical individuals attend to the eyes when scanning faces (Haith et al 1977) as well as the internal features of the face (Janik et al 1978;Walker-Smith et al 1977). Furthermore, eye movements become more predictable with increased exposure and familiarity (Althoff and Cohen 1999), suggesting that exposure to a face can influence eye movements, or patterns of attention to faces.…”
Section: Eye Tracking and Familiar Facesmentioning
confidence: 99%
“…We will focus on the latter. Research on gaze behavior during face processing in healthy populations is in high agreement that participants fixate first and foremost the eyes and mouth when no instructions are given prior to viewing the faces (Groner, Walder, & Groner 1984;Janik, Wellens, Goldberg, & Dell'Osso, 1978;Yarbus, 1967). Jeffreys, Tukmachi, and Rockley (1992) studied the relationship between evoked potential and fixation position with facial images and concluded that the point between both eyes might be the position from which optimal processing occurs.…”
Section: Research On Gaze Behavior During Face Processingmentioning
confidence: 99%
“…People attend to the eyes at least 40% of the time, which is far greater than attention to other principal facial features such as the nose and mouth (Henderson, Williams, & Falk, 2005;Janik, Wellens, Goldberg, & Dell'Osso, 1978). Research has demonstrated that the eyes provide access to data useful for a variety of social judgments (Looser & Wheatley, 2010;Macrae, Hood, Milne, Rowe, & Mason, 2002;Niedenthal et al, 2010).…”
Section: Preferential Attention To the Eyes Of Ingroup Membersmentioning
confidence: 99%